Development of Digital Talents Millennial Muslims in Facing the Digitalization of Sharia Economy in the Era Society 5.0 - Husni Awali; Farida Rohmah (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Objectives: This study aims to develop a conceptual framework for digital talent development among millennial Muslims in supporting the digitalization of the sharia economy in the Society 5.0 era.Methodology: Qualitative research using the Literature Review approach and conceptual review techniques, in which with this method the researcher seeks to collect various data and information from various academic literature that has suitability and relevance to the topics used in this study in order to obtain an understanding and concept regarding the development of digital talent, especially for Muslims. millennials in facing the digitalization of the Islamic economy in the era of society 5.0.Finding: Sharia economic actors in addition to transforming into business digitalization also need to develop their human resources so that they have a Critical Thinking soul and instill the values of Creativity, Collaboration and Communication and are supported by digital HR, supporting technology, research and innovation as a form of facing the Digitalization of the sharia economy in the era of society 5.0.Conclusion: This study contributes by offering an integrative framework that links digital talent development with sharia economic transformation, particularly within the socio-religious context of millennial Muslims.